THE EFFECT OF SELF CHECK-IN FACILITIES ON PASSENGER SATISFACTION AT SENTANI INTERNATIONAL AIRPORT - Ukkasyah Sabbit Aqdamana Lubis; Dimas Endrawan Putra; Willyam Evander R (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Purpose - This research aims to measure the influence of self check-in facilities on passenger satisfaction at Sentani International Airport. Methodology - A quantitative approach was employed using survey methodology through data collection using questionnaires distributed to 100 respondents. Research Findings - The results demonstrate that self check-in facilities exert a significantly positive influence on passenger satisfaction, contributing 62.7% to overall satisfaction levels. Validity and reliability testing yielded satisfactory results, and regression analysis revealed that each 1% improvement in self check-in facilities increased passenger satisfaction by 0.794 units. Originality - This research provides new insights regarding the importance of self check-in facilities in enhancing passenger experience, which can serve as a foundation for service improvements at airports, particularly from the perspective of airport user satisfaction and customer service delivery. The research contributes to the broader understanding of how digital transformation in airport operations directly impacts customer experience metrics and operational efficiency.